2014
DOI: 10.1016/j.devcel.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Shape Modulates Transmembrane Protein Distribution

Abstract: Summary Although membrane shape varies greatly throughout the cell, the contribution of membrane curvature to transmembrane protein targeting is unknown due to the numerous sorting mechanisms taking place concurrently in cells. To isolate the effect of membrane shape, cellsized Giant Unilamellar Vesicles (GUVs) containing either the potassium channel, KvAP, or water channel, AQP0, were used to form membrane nanotubes with controlled radii. While the AQP0 concentrations in flat and curved membranes were indisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
227
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(239 citation statements)
references
References 38 publications
12
227
0
Order By: Relevance
“…On the chemical side, bilayers exhibit nonlinear chemical effects as a result of molecular crowding, such as nonlinear adsorption (Sorre et al, 2012) or nonlinear sorting of proteins between vesicles and tubules (Zhu et al, 2012;Aimon et al, 2014;Prévost et al, 2015). Thus, linearized chemo-mechanical models can only provide information about the onset of transitions (Shi and Baumgart, 2015), about dilute concentrations of protein on the surface (Góźdź, 2011), or about the response under very small perturbations (Callan-Jones et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…On the chemical side, bilayers exhibit nonlinear chemical effects as a result of molecular crowding, such as nonlinear adsorption (Sorre et al, 2012) or nonlinear sorting of proteins between vesicles and tubules (Zhu et al, 2012;Aimon et al, 2014;Prévost et al, 2015). Thus, linearized chemo-mechanical models can only provide information about the onset of transitions (Shi and Baumgart, 2015), about dilute concentrations of protein on the surface (Góźdź, 2011), or about the response under very small perturbations (Callan-Jones et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we call these objects that induce isotropic spontaneous curvature an isotropic inclusion. Their assembly into preferred curvature regions [23][24][25][26][27] and membrane-mediated interactions between the colloids [28][29][30] have been previously explored.…”
Section: Introductionmentioning
confidence: 99%
“…Such fluctuations have an effect on the membrane as well as the inclusion shape. Indeed, unlike [5,10], we find above that by taking into account thermal fluctuations we are also able to accurately capture the membrane tension dependent mobility of an AQP0 inclusion even when its average contact angle ( β ∼ β 0 ) vanishes (β 0 ∼ 0) [22]. Furthermore, using our theory we can now be seen to be able to directly probe and investigate inclusion elasticity (governed by the elastic constant k p ) via measurements of the inclusion's mobility.…”
Section: Discussionmentioning
confidence: 99%
“…In [5] it was found that the diffusion constant for a voltage-gated potassium channel (KvAP) protein was significantly increased, as the surface tension was increased, whereas the mobility of a water channel aquaporin 0 (AQP0) protein was, relatively, fairly insensitive to membrane tension. This is thought to occur due to the fact that KvAP locally bends the membrane considerably, forming an effectively conical inclusion, whereas AQP0 is thought to negligibly deform the bilayer locally [5,22]. Shown in fig.…”
Section: Comparison With Recent Experimental Datamentioning
confidence: 99%